Design thinking approach with cognitive internship model to improve innovative attitudes of teachers professional education students - Sumantri, Mohamad Syarif; Khasanah, Uswatun; Suntari, Yustia; Agustin, Nadya Dewinda (American Journal of Education and Learning, 2025)
The educational aspect that drives teachers to perform their responsibilities is one of many aspects that affect the quality of their performance which is very challenging. The quality of education is currently considered low because it cannot fully provide competence by the educational stage undergone by prospective teacher students. The purpose of this initiative is to improve the innovative attitude of teachers and professional education students by using a design thinking method to create learning activities using a cognitive internship model and by performing comprehensive studies and research. This research design uses action research with more emphasis on the process of trying new things. The subject of this study is teaching professional education students in the odd semester of 2023-2024 at the State University of Jakarta with a total of 94 students. The research was conducted for six months. Data analysis is used in qualitative and quantitative ways to obtain data on the process and improvement of learning activities in improving students' innovative attitudes. The results of the study showed an increase in 5 indicators of developing students' innovative attitudes, namely 1) innovative learning design projects, 2) reflection and self-evaluation, 3) case studies of educational innovation, 4) collaboration with the business world and industry and 5) innovative idea competition. In the pre-cycle, it scored 2.7%, the first cycle got a score of 3.4%, and the second cycle got a score of 4.0%. It can be concluded that integrating design thinking with the cognitive internship model in improving the innovative attitude of teacher professional education students have proven to be effective with five indicators developed in this study.